2008
DOI: 10.1158/1078-0432.ccr-07-4608
|View full text |Cite
|
Sign up to set email alerts
|

Are There Any Ethnic Differences in Molecular Predictors of Erlotinib Efficacy in Advanced Non-Small Cell Lung Cancer?

Abstract: Purpose: This study investigated possible molecular predictors of outcome in Korean patients with advanced non-small cell lung cancer treated with erlotinib. Experimental Design: One hundred and twenty patients received erlotinib and were followed prospectively. Ninety-two tissue samples were analyzed for epidermal growth factor receptor (EGFR) gene mutations (exons 18, 19, and 21), 88 for EGFR gene amplification by real-time PCR, and 75 for EGFR protein expression by immunohistochemistry. Results:The overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
33
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 20 publications
5
33
0
Order By: Relevance
“…16 Recently, we reported that the incidence of EGFR mutations for all patients who were treated with erlotinib was higher (26.1%) in Korean patients when compared with Western countries (<10%). 17 This is consistent with previously reported data. Therefore, the high response rate in this analysis might be explained because of high EGFR-positive rate.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…16 Recently, we reported that the incidence of EGFR mutations for all patients who were treated with erlotinib was higher (26.1%) in Korean patients when compared with Western countries (<10%). 17 This is consistent with previously reported data. Therefore, the high response rate in this analysis might be explained because of high EGFR-positive rate.…”
Section: Discussionsupporting
confidence: 94%
“…17,20 More recently, ISTANA (IRESSA as Second-Line Therapy in Advanced NSCLC-Korea) showed longer PFS and a significantly improved overall response rate compared with docetaxel in Korean patients. 21 It is unclear why no survival benefit with gefitinib was found in the Iressa Survival Evaluation in Lung Cancer study, despite apparent similar antitumor activity as that seen in previous studies with erlotinib.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current focus is on the predictive power of EGFR mutations, a high EGFR gene copy number, and k-ras mutations (Eberhard et al, 2005;Shepherd et al, 2005;Ahn et al, 2008). Unfortunately, standardised clinical tests for the molecular predictors of erlotinib treatment outcome are expensive and not readily accessible in most hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Many publications have shown that EGFR mutations are associated with increased EGFR gene copy number and EGFR expression. EGFR gene mutations and increased amplification were found to be the best parameter in determining clinical progression in the Korean patients treated with erlotinib [32] and in Japanese patients treated with gefitinib [5]. In addition, researchers have suggested investigating the effects of these molecular markers in different ethnic groups.…”
Section: Discussionmentioning
confidence: 99%